Occurrence of various viruses and recent evidence of SARS-CoV-2 in wastewater systems - Ali, Waqar; Zhang, Hua; Wang, Zhenglu; Chang, Chuanyu; Javed, Asif; Ali, Kamran; Du, Wei; Niazi, Nabeel Khan; Mao, Kang; Yang, Zhugen (Elsevier, 2021)
Viruses are omnipresent and persistent in wastewater, which poses a risk to human health. In this review, we summarize the different qualitative and quantitative methods for virus analysis in wastewater and systematically discuss the spatial distribution and temporal patterns of various viruses (i.e., enteric viruses, Caliciviridae (Noroviruses (NoVs)), Picornaviridae (Enteroviruses (EVs)), Hepatitis A virus (HAV)), and Adenoviridae (Adenoviruses (AdVs))) in wastewater systems. Then we critically review recent SARS-CoV-2 studies to understand the ongoing COVID-19 pandemic through wastewater surveillance. SARS-CoV-2 genetic material has been detected in wastewater from France, the Netherlands, Australia, Italy, Japan, Spain, Turkey, India, Pakistan, China, and the USA. We then discuss the utility of wastewater-based epidemiology (WBE) to estimate the occurrence, distribution, and genetic diversity of these viruses and generate human health risk assessment. Finally, we not only promote the prevention of viral infectious disease transmission through wastewater but also highlight the potential use of WBE as an early warning system for public health assessment.
Keywords: Viruses; SARS-CoV-2; Spatial distribution; Wastewater; Human health hazards